2022
DOI: 10.3390/molecules27030750
|View full text |Cite
|
Sign up to set email alerts
|

New Imatinib Derivatives with Antiproliferative Activity against A549 and K562 Cancer Cells

Abstract: Tyrosine kinase enzymes are among the primary molecular targets for the treatment of some human neoplasms, such as those in lung cancer and chronic myeloid leukemia. Mutations in the enzyme domain can cause resistance and new inhibitors capable of circumventing these mutations are highly desired. The objective of this work was to synthesize and evaluate the antiproliferative ability of ten new analogs that contain isatins and the phenylamino-pyrimidine pyridine (PAPP) skeleton, the main pharmacophore group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Copper-catalyzed 1,3-dipolar cycloaddition (CuAAC) to form 1,2,3-triazoles is the most popular reaction in click chemistry. Recently, 1,2,3-triazole backbones with hydrogen bonds, moderate dipole moments and enhanced water solubility had been widely used to generate drug candidates of anti-tumor ( Brown et al, 2022 ; Elganzory et al, 2022 ; Mohammed et al, 2022 ; Oekchuae et al, 2022 ; Oliveira et al, 2022 ; Mironov et al, 2023 ), anti-seizure ( Bhattacherjee et al, 2022 ), anti-diabetic ( Dhameja et al, 2022 ), anti-parasitic ( Aljohani et al, 2022 ), anti-bacterial ( Daher et al, 2022 ; Mokariya et al, 2022 ; Nsira et al, 2022 ) and anti-viral ( Kutkat et al, 2022 ; Tatarinov et al, 2022 ) via CuAAC click chemistry ( Figure 1A ).…”
Section: Click Chemistrymentioning
confidence: 99%
“…Copper-catalyzed 1,3-dipolar cycloaddition (CuAAC) to form 1,2,3-triazoles is the most popular reaction in click chemistry. Recently, 1,2,3-triazole backbones with hydrogen bonds, moderate dipole moments and enhanced water solubility had been widely used to generate drug candidates of anti-tumor ( Brown et al, 2022 ; Elganzory et al, 2022 ; Mohammed et al, 2022 ; Oekchuae et al, 2022 ; Oliveira et al, 2022 ; Mironov et al, 2023 ), anti-seizure ( Bhattacherjee et al, 2022 ), anti-diabetic ( Dhameja et al, 2022 ), anti-parasitic ( Aljohani et al, 2022 ), anti-bacterial ( Daher et al, 2022 ; Mokariya et al, 2022 ; Nsira et al, 2022 ) and anti-viral ( Kutkat et al, 2022 ; Tatarinov et al, 2022 ) via CuAAC click chemistry ( Figure 1A ).…”
Section: Click Chemistrymentioning
confidence: 99%
“…The second pathway involved propargylation of the appropriate cyclic amine, 2-mercaptobenzothiazole or isatin derivative in the presence of potassium carbonate and DMF (Scheme 1) and afforded the propargylated derivatives (4f-4q) in 76-83% yield. [64][65][66][67][68][69][70] Finally, the target 1,2,3-triazoles (5a-5q) were obtained in 76-89% yield via Cu-catalyzed click cycloaddition of 3a with the alkyne or propargylated derivatives (4f-q) under standard conditions. All 5a-q were fully characterized using IR, 1 H-NMR, 13 C-NMR, ESI-MS and elemental analyses.…”
Section: Chemistrymentioning
confidence: 99%
“…Synthesis of propargylated un/5-substituted isatins (4k-p). [67][68][69] To a solution of 5-(un)substituted isatin (3.36 mmol, 1 equivalent) in DMF (3 mL) was added K 2 CO 3 (1.39 g, 10.08 mmol, 3 equivalent) and the mixture was stirred for ¼ h, then propargyl bromide (80% wt in toluene, 0.6 mL, 4.04 mmol, 1.2 equivalent) was added and the reaction mixture was stirred at room temperature for 3 h. Upon addition of H 2 O (15 mL), the propargylated isatins were precipitated, filtered, washed with H 2 O and recrystallized from EtOH/H 2 O and air dried (% yield and melting points are listed in Table 5).…”
Section: Rsc Medicinal Chemistry Research Articlementioning
confidence: 99%
“…Some of the pyridine-containing 1,2,3-triazole-pyrimidine hybrids also showed decent antileukemic activity, [50,51] 2.06-27.05 µM, MTT assay) were active against stem cell-like KG-1a leukemia cells, and the SAR indicated that cyclic amino group at the C-4 position of 1,2,3-triazole was favorable to the activity. [52] In particular, hybrids 17a,b (IC 50 : 2.06 and 3.28 µM) were 4.3-and 3.0fold more potent than the parent lapatinib (IC 50 : 9.76 µM) against stem cell-like KG-1a leukemia cells, and hybrid 17a (IC 50 : 6.24 and 5.39 µM) also showed higher activity than lapatinib (IC 50 : 20.11 and 12.14 µM) against SKBR3 and SUM159 breast cancer cell lines.…”
Section: 23-triazole-pyrimidine/ Nucleoside Hybridsmentioning
confidence: 99%
“…Some of the pyridine‐containing 1,2,3‐triazole‐pyrimidine hybrids also showed decent antileukemic activity, [ 50,51 ] and amongst them, hybrids 16a,b (IC 50 : 1.0 and 2.3 µM, MTT assay) were active against K562 cells. The SAR revealed that the amide linker between 1,2,3‐triazole and phenyl ring was essential for the activity, and replacement by amine led to a significant loss of activity.…”
Section: 23‐triazole‐pyrimidine/nucleoside Hybridsmentioning
confidence: 99%